Adoption of Improved Dairy Cows and Implications for Household Food Security: Evidence in Central Highland of Ethiopia (Global Journal of Science Frontier Research, 2017)
Crop-livestock production is the main livelihood strategy for rural households of Ethiopia. However, it is constrained by low level of adoption for agricultural technologies. The objectives of this study are, therefore: analyzing adoption of dairy cow technology and examining the contribution of the technology to household food security. The study is conducted in Gudo Beret watershed, North Shewa, Ethiopia. Primary and secondary data were collected from different sources. In the watershed, 211 respondents were selected through systematic random sampling. Expert consultation, household interview, key informants, focused groups, and personal observation were the main data collection methods. Descriptive statistics, inferential tests, multivariate tools, and econometric models have used for data analysis.
Keywords: adoption; dairy cow; food security; logit model